2013
DOI: 10.1177/0269881113477747
|View full text |Cite
|
Sign up to set email alerts
|

The effects of the phosphodiesterase type 5 inhibitor vardenafil on cognitive performance in healthy adults: a behavioral- electroencephalography study

Abstract: Phosphodiesterase type 5 inhibitors (PDE5-Is) improve cognitive performance of rodents, but the few human studies investigating their effects did not systematically investigate cognitive effects and the results have been quite contradictory. Therefore, we examined whether the PDE5-I vardenafil improves memory and executive functioning and affect electroencephalography (EEG) in healthy young adults. Participants were selected out of a group of volunteers, based on their performance on a memory screening and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
(58 reference statements)
0
24
0
Order By: Relevance
“…Acute administration of a PDE5 inhibitor had no effects on cognition in healthy subjects [46,47,49]. Yet despite these negative findings we still cannot rule out inhibition of PDE5 as a treatment for cognitive impairment and/or AD.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Acute administration of a PDE5 inhibitor had no effects on cognition in healthy subjects [46,47,49]. Yet despite these negative findings we still cannot rule out inhibition of PDE5 as a treatment for cognitive impairment and/or AD.…”
Section: Resultsmentioning
confidence: 99%
“…verbal learning test) [48,49]. Memory and executive functioning were tested while EEG activity was recorded.…”
Section: Vardenafilmentioning
confidence: 99%
“…However, these tests are well established tests for studying human memory and should be sensitive enough to pick up any effects. Furthermore, the 20-mg dose of vardenafil used is comparable to effective doses in animals (Reneerkens et al 2013a). In previous studies with healthy non-impaired humans, a ceiling effect might also have attenuated any improved cognition/ memory performance.…”
Section: Discussionmentioning
confidence: 98%
“…Clinical studies demonstrated that while a single dose of sildenafil does not cause a clear improvement in cognition in healthy adults [172], chronic administration of udenafil has shown to lead to an improvement in cognitive function [130]. This has led some to suggest that the therapeutic benefits of PDE5-Is may be better observed after chronic inhibition rather than after a single dose [173]. However, studies evaluating the anti-inflammatory effects of chronic PDE5-Is in PD models are lacking.…”
Section: Parkinson's Disease and Huntington's Diseasementioning
confidence: 99%